2008
DOI: 10.1093/jnci/djn310
|View full text |Cite
|
Sign up to set email alerts
|

Cause-Specific Late Mortality Among 5-Year Survivors of Childhood Cancer: The Childhood Cancer Survivor Study

Abstract: Our extended follow-up of 5-year survivors of pediatric and adolescent cancer indicates that excess mortality persists long after diagnosis. Continued observation is needed to further define lifetime risk and to determine the potential contribution of chronic health conditions and modifiable health behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
488
3
15

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 624 publications
(519 citation statements)
references
References 28 publications
(9 reference statements)
13
488
3
15
Order By: Relevance
“…In line with other childhood and YA cancer studies, early onset cancer survivors showed significantly increased SMRs due to cardiovascular conditions. 4,7,11 In addition to that, the elevated HRs regarding all investigated subgroups of cardiovascular causes of death in early onset cancer survivors compared to siblings emphasized the role of cancer and its therapy on cardiovascular mortality. HR values in the first treatment era did not decrease until 1990 concerning cardiovascular deaths underlining the lacking improvement with respect to cardiovascular late effects of cancer and its therapy.…”
Section: Epidemiologymentioning
confidence: 95%
See 4 more Smart Citations
“…In line with other childhood and YA cancer studies, early onset cancer survivors showed significantly increased SMRs due to cardiovascular conditions. 4,7,11 In addition to that, the elevated HRs regarding all investigated subgroups of cardiovascular causes of death in early onset cancer survivors compared to siblings emphasized the role of cancer and its therapy on cardiovascular mortality. HR values in the first treatment era did not decrease until 1990 concerning cardiovascular deaths underlining the lacking improvement with respect to cardiovascular late effects of cancer and its therapy.…”
Section: Epidemiologymentioning
confidence: 95%
“…23 In our study, cumulative mortality due to cardiovascular disease in both, childhood and YA cancer survivors, showed a markedly increasing tendency particularly after 25 years from diagnosis, emphasizing the necessity for long-term follow-up and surveillance for cardiac complications, as observed in earlier childhood cancer studies. 4,7,25 Among all early onset cancer survivors, HL survivors had the highest late cumulative mortality due to cardiovascular diseases and also the shortest time lag from diagnosis until this increase. In line with our findings, Aleman et al stated that after 10 years from HL diagnosis, mortality causes other than relapse, such as cardiovascular diseases prevailed in this cancer survivor group.…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations